2021
DOI: 10.51970/jasp.1019391
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Uygulanan Tekelerde Aşım Davranışları ve Hormon Profili

Abstract: In this study, the effects of melatonin implant treatment before the breeding season on melatonin (M) and testosterone (T) hormone levels, and the mating behavior and performance, were determined in Turkish Saanen goat bucks. Four head of bucks and 50 head of goats were used. The bucks were randomly divided into two groups and they were treated with 3 implants with 18 mg melatonin. The half of female goats were also implanted with melatonin (18 mg/goat). A total of 13 blood samples were collected before the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Exposing farm animals especially males to hot environment will increase respiratory rate and rectal temperature (Spiers et al 2004 and Avendono-Reyes et al 2011), temperature of the body surface (Martello et al 2009) and heart rate (Zahner et al, 2004) which could ultimately affect the breeding ability of such animal. However, Tölü, et al (2021) reported amelioration of this effect in melatonin treated bucks with positive effects on mating frequency. The haematological profile in goats has also been seen to be generally influenced by several physiological factors (Tambuwal et al, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…Exposing farm animals especially males to hot environment will increase respiratory rate and rectal temperature (Spiers et al 2004 and Avendono-Reyes et al 2011), temperature of the body surface (Martello et al 2009) and heart rate (Zahner et al, 2004) which could ultimately affect the breeding ability of such animal. However, Tölü, et al (2021) reported amelioration of this effect in melatonin treated bucks with positive effects on mating frequency. The haematological profile in goats has also been seen to be generally influenced by several physiological factors (Tambuwal et al, 2002).…”
Section: Introductionmentioning
confidence: 97%